A Different Perception of Hybrid Renewable Energy Sources Integrated Multi-objective Optimal Power Flow considering Performance Parameters and Penetration. Issue 3 (3rd July 2021) - Pandya, Sundaram B.; Jariwala, Hitesh R.
ABSTRACT: Traditional generating units, as well as renewable energy resources, make up the electrical grid. The proposed article proposes performance indices for optimal power flow, which combine wind turbines, solar photovoltaic systems, and hybrid solar with small hydropower sources. The irregularity of renewable energy sources' performance adds to the complexity of the optimal power flow (OPF) problem. The analytical strategies also use lognormal, Weibull, and Gumbel probability density functions to approximate the energy yield of those renewables. Also explored is the effect of changing distribution parameters and the penetration of renewable energy resources as a function of optimal power flow. Penalty charges for underestimation and standby charges for overestimation of unusual non-conventional generating units are included in the objective feature. The optimization problem is solved using a non-dominated multi-objective moth flame optimization technique. In terms of achieving diverse and convergent Pareto optimal solutions, the MOMFO optimizer is more efficient and robust than the SMODE/SF and MOEA/D-SF optimizers, according to the simulation outcomes. As a result IEEE-30 bus system, the MOMFO optimizer can be used to tackle the MO-SCOPF issue with the incorporation of wind, solar, hydro, and thermal generators in an integrated multiple-power system. GRAPHICAL ABSTRACT: uf0001